EVALITA Evaluation of NLP and Speech Tools for Italian - December 17th, 2020 Proceedings of the Seventh Evaluation Campaign of Natural Language Processing and Speech Tools for Italian Final Workshop - Basile, Valerio; Croce, Danilo; Maro, Maria; Passaro, Lucia C. (Collana dell'Associazione Italiana di Linguistica Computazionale, 2020)
Welcome to EVALITA 2020! EVALITA is the evaluation campaign of Natural Language Processing and Speech Tools for Italian. EVALITA is an initiative of the Italian Association for Computational Linguistics (AILC, http://www.ai-lc.it) and it is endorsed by the Italian Association for Artificial Intelligence (AIxIA, http://www.aixia.it) and the Italian Association for Speech Sciences (AISV, http://www.aisv.it).